ADAPTASI IDENTITAS ANAK PELAKU WAYANG BOCAH DI LINGKUNGAN SEKOLAH MODERN - Suparti; Widodo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This qualitative case study explores the identity adaptation and psychological impacts on children performing in Wayang Bocah within a modern school ecosystem. Integrating Social Identity Theory and Social Construction Theory, this study examines children's dynamics across two contradictory domains: traditional art studios and public schools. Data were gathered through in-depth interviews, participant observation, and documentary analysis involving child actors, parents, and teachers. The results reveal a phenomenon of